CGIAR Road from COP29 to COP30 Webinar Series #4 | The Just Transition Work Programme (JTWP) - CGIAR Science Program on Climate Action (2025)
The CGIAR Road from COP29 to COP30 Fireside Chat Series convenes global experts to unpack the negotiation tracks shaping climate finance and adaptation ahead of COP30.This session turns to the Just Transition Work Programme (JTWP),a critical and evolving track established at COP27 to ensure that climate action is fair, inclusive, and aligned with national development priorities. The JTWP supports implementation of Article 2.1(c) of the Paris Agreement by fostering low-emission, climate-resilient development that leaves no one behind.